الكتابات النسوية المغاربية بين برهان العقل و سلطان الجنس - طهراوي مبروكة; العايب يوسف (University of Eloued جامعة الوادي, 2025)
تعتبر النسوية من أكثر الحركات الحداثية إشكالا وجدلا حتى على مستوى مجتمعاتها الغربية التي أنتجتها ،نظرا لأنها تصنّف كردة فعل على فعل ذكوري دهري، فقد كانت وليدة الغياب القسري الذي فرضته الميتافيزيقا الغربية، وذكورية الفكر الإنساني برمته، فكانت على الدوام الضمير الغائب المكتوب عنه،والفعل المبني للمجهول،لكن ببزوغ فجر الحداثة دخلت المرأة ببعض أطيافها و تنوعاتها في دائرة الضوء،فأصبحت تتكلم عن ننفسها بضمير الأنا،ثائرة عن كل الصور التنميطية التي كرستها لها الكتابات الذكورية عبر العصور، فكانت الكتابة النسوية كائنا ثقافيا جديدا في الغرب ، ثم في المشرق العربي و مغربه،وهذا الأخير كانت فيه أقلام نسائية رائدة و ناطقة باسم المرأة العربية في تقلباتها الحضارية والنفسية:مظلومة،منصورة ،مستهامة شهوانية،حكيمة،حرة....امرأة تخوض حروب التحرير النسقية ضد العرفية الذكورية داخل ذاتها وفي تلافيف لاشعورها من جانب، و تخوض معارك الواقع مع الرجل وامبراطوريته الثقافية التي تحتوي فيما تحتويه حتى اللغة التي تعتصم بها المرأة الكاتبة لتنصرها. فإلى أي حدّ ستكون اللغة متواطئة مع الرجل ،وتقف ضد الكاتبة المرأة ؟ و هل الكتابة النسوية ينتجها الوعي والفعل؟أم اللواعي وردة الفعل ؟ و إلى أي درجة تعتبر الكتابات النسوية المغاربية ممثلا شرعيا وناطقا أمينا بـهموم المرأة المغاربية في كل نسخها الرسمية و الشعبية؟ وهل يمكننا القول أن الكتابات النسوية التي تتطابق مع استيهامات العرف الذكوري وشهوانيته هي كتابات غير نسوية ولو كانت كاتبتها امرأة؟ وأن كتابات العقل المدافعة عن الحق النسوي ولو كان كاتبها رجل تعتبر نسوية؟ Feminism is considered one of the most problematic and controversial modernist movements, even at the level of the Western societies that produced it, because it is classified in the circle of reaction. It was the result of the forced absence imposed by Western metaphysics and the masculinity of human thought. It was always the absent conscience written about, and when the sun rose In modernity, women, with all their spectrums and diversities, entered the spotlight and began to speak about themselves with the ego conscience, revolting against all the stereotypical images that male writings had devoted to them throughout the ages. Feminist writing was a new cultural entity in the West, then in the Arab East and West, the latter whose pens were Feminism is a pioneer and a spokesperson for the Arab woman in her cultural and psychological fluctuations: oppressed, victorious, neglected, lustful, wise, free........a woman who fights wars of liberation against the traditional masculine system within herself and in the recesses of her subconscious, fighting the battles of reality with the man and his empire. The cultural language that includes, among other things, even the language that the woman writer uses to support her, so to what extent will the language be complicit with the man, and stand against the woman writer? Is feminist writing produced by awareness and action? Or by unconsciousness and reaction What is feminist writing? To what extent is Maghreb feminist writing considered a legitimate and faithful representative of Maghreb women in all its official and popular versions?
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع 02
Keywords: الكتابة النس; ية; الحداثة; العقل; الجنس; فاطمة المرنيسي; أحلام مستغانمي